2009
DOI: 10.1002/app.30570
|View full text |Cite
|
Sign up to set email alerts
|

Free‐radical retrograde‐precipitation copolymerization of vinyl acetate and acrylic acid

Abstract: Free-radical chain polymerization kinetics of vinyl acetate (VA) and acrylic acid (AA) exhibit some unusual control features. The VA radicals have a high rate of chain transfer leading to relatively sluggish propagation rates. Polymerization of AA, however, is prone to autoacceleration behavior in bulk, solution, and precipitating media. Thus, conventional statistical copolymerization of VA and AA would result in the preferential formation of high AA content copolymer. However, when the reaction medium is chos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The acceleration of the rate of polymerization of some monomers by Pd II has been observed [12,13]. Polymerization of methylmethacrylate (MMA) initiated by amines in the presence of CCl 4 by a charge-transfer mechanism [14][15][16][17][18][19][20][21][22][23][24][25], amines, and Ru III complexes is also a very effective system in atom transfer radical polymerization mechanism [26,27], and a free-radical retrograde-precipitation polymer mechanism has been studied widely by many investigators [28][29][30][31][32][33][34][35]. It has been observed that two different mechanisms [36,37] for the initiation of polymerization of MMA, involving the charge-transfer complex formed by the interaction of amine and CCl 4 -under the conditions [CCl 4 /amine]≤1-and by the interaction of amine and MMA-under the conditions [CCl 4 /amine]≥1 have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The acceleration of the rate of polymerization of some monomers by Pd II has been observed [12,13]. Polymerization of methylmethacrylate (MMA) initiated by amines in the presence of CCl 4 by a charge-transfer mechanism [14][15][16][17][18][19][20][21][22][23][24][25], amines, and Ru III complexes is also a very effective system in atom transfer radical polymerization mechanism [26,27], and a free-radical retrograde-precipitation polymer mechanism has been studied widely by many investigators [28][29][30][31][32][33][34][35]. It has been observed that two different mechanisms [36,37] for the initiation of polymerization of MMA, involving the charge-transfer complex formed by the interaction of amine and CCl 4 -under the conditions [CCl 4 /amine]≤1-and by the interaction of amine and MMA-under the conditions [CCl 4 /amine]≥1 have been proposed.…”
Section: Introductionmentioning
confidence: 99%